On fuzzy semi δ – V continuity in fuzzy δ – V topological space - Mukherjee, A.; Halder, S. (Український математичний журнал, 2008)
New concepts of fuzzy semi δ – V and fuzzy semi δ – Λ sets were introduced in the work „On fuzzy semi δ – Λ sets and fuzzy semi δ – V sets V – 6” by the authors (J. Trip. Math. Soc., 6, 81 – 88 (2004)). It was shown that the family of all fuzzy semi δ – V sets forms a fuzzy supra topological space on X denoted by ( X, FS δV ). The aim of this paper is to introduce the concept of fuzzy semi δ – V continuity in a fuzzy δ – V topological space. Finally, some properties, preservation theorems, etc., are studied.